Proteomic changes associated with expression of a gene (ipt) controlling cytokinin synthesis for improving heat tolerance in a perennial grass species - Xu, Yan (Journal of experimental botany, 2010)
Cytokinins (CKs) are known to regulate leaf senescence and affect heat tolerance, but mechanisms underlying CK regulation of heat tolerance are not well understood. A comprehensive proteomic study was conducted to identify proteins altered by the expression of the adenine isopentenyl transferase (ipt) gene controlling CK synthesis and associated with heat tolerance in transgenic plants for a C(3) perennial grass species, Agrostis stolonifera. Transgenic plants with two different inducible promoters (SAG12 and HSP18) and a null transformant (NT) containing the vector without ipt were exposed to 20 degrees C (control) or 35 degrees C (heat stress) in growth chambers. Two-dimensional electrophoresis and mass spectrometry analysis were performed to identify protein changes in leaves and roots in response to ipt expression under heat stress. Transformation with ipt resulted in protein changes in leaves and roots involved in multiple functions, particularly in energy metabolism, protein destination and storage, and stress defence. The abundance levels of six leaf proteins (enolase, oxygen-evolving enhancer protein 2, putative oxygen-evolving complex, Rubisco small subunit, Hsp90, and glycolate oxidase) and nine root proteins (Fd-GOGAT, nucleotide-sugar dehydratase, NAD-dependent isocitrate dehydrogenase, ferredoxin-NADP reductase precursor, putative heterogeneous nuclear ribonucleoprotein A2, ascorbate peroxidase, dDTP-glucose 4-6-dehydratases-like protein, and two unknown proteins) were maintained or increased in at least one ipt transgenic line under heat stress. The diversity of proteins altered in transgenic plants in response to heat stress suggests a regulatory role for CKs in various metabolic pathways associated with heat tolerance in C(3) perennial grass species